2014
DOI: 10.1039/c3ta13951d
|View full text |Cite
|
Sign up to set email alerts
|

High-surface-area ordered mesoporous oxides for continuous operation in high temperature energy applications

Abstract: The collapse of nanostructures at high temperature is one of the main drawbacks for the implementation of nanomaterials in some energy applications. An exciting virtual non-degradation up to 1000 C is presented here for ordered mesoporous gadolinia doped ceria. By using the nanocasting method based on the KIT-6 template, the long-term stability of the material is achieved when extending the self-limited grain growth regime, recently proved for thin films, to open three-dimensional structures. Contrary to widel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…5 This process needs to be competitive and to exhibit high performance and long-term stability in order to enter the energy market. 6 Solid oxide electrolysers operate at high temperature, thus having clear thermodynamic and kinetic advantages. This results in fast charge (e.g., charge transfer or electrical conduction) and mass transport and low internal resistance, thus leading to low electrical demand and high efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…5 This process needs to be competitive and to exhibit high performance and long-term stability in order to enter the energy market. 6 Solid oxide electrolysers operate at high temperature, thus having clear thermodynamic and kinetic advantages. This results in fast charge (e.g., charge transfer or electrical conduction) and mass transport and low internal resistance, thus leading to low electrical demand and high efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…An example of an electroceramic cathode is shown in Figure 15.7(a), that is, an La 0.6 Sr 0.4 CoO 3-d mesoporous thin film deposited by PLD. This material is one of the best-performing cathodes for IT-SOFCs (Mauvy et al, 2004) and for such morphology, gas exchange is greatly enhanced by large exposition of the surface to the gas (such mesoporous material can easily achieve surface area above 100e200 m 2 /g (Almar et al, 2014)). Porous thin films with fine and ultrafine porosity are usually deposited by PVD methods at low temperatures (i.e., at low mass diffusion regimes, where nanometric particles rapidly condense and bond at the electrolyte by including porosity).…”
Section: Nano-design In Cathode Thin Filmmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] The usage of mesostructured metal oxides as the active cathode material of lithium ion batteries is advantageous mainly due to (i) an increase of the contact area between the electrolyte and the cathode material, (ii) an increase of the lithium ion diffusion rate into and within the cathode material, resulting in an overall improved cell performance. It has been shown that an insufficient transport of lithium ions into the cathode active material can lead to cell degradation reactions, which are further promoted by a successive accumulation of lithium ions on the surface of the cathode material.…”
Section: Introductionmentioning
confidence: 99%